1951
DOI: 10.2307/3755649
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Nutrition of Morchella esculenta Fries

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
15

Year Published

1956
1956
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 22 publications
0
12
0
15
Order By: Relevance
“…L-asparagin has been reported to be a good source by SAKSENA and KUMAR (1961) and KURTZ and FERGUS (1964). Nevertheless, MOSHER et al (1936), STEINBERG (1942) and BROCK (1951) found DL-valine to be of poor nutritive value for Trichophyton interdigitahy Aspergillus nigcr and Morchella esculenta respectively, while LoGKwooD et al (1936), WOLF (1949) and WOLF et al (1950) obtained only moderate growth of their organisms on alanine. Further, CHANDRA (1961) reported only poor growth of Cercosporina ricinella on glutamic acid, and DAS GUPTA and SHOME (1960) could not obtain any growth of Trichophyton rubrum on this amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…L-asparagin has been reported to be a good source by SAKSENA and KUMAR (1961) and KURTZ and FERGUS (1964). Nevertheless, MOSHER et al (1936), STEINBERG (1942) and BROCK (1951) found DL-valine to be of poor nutritive value for Trichophyton interdigitahy Aspergillus nigcr and Morchella esculenta respectively, while LoGKwooD et al (1936), WOLF (1949) and WOLF et al (1950) obtained only moderate growth of their organisms on alanine. Further, CHANDRA (1961) reported only poor growth of Cercosporina ricinella on glutamic acid, and DAS GUPTA and SHOME (1960) could not obtain any growth of Trichophyton rubrum on this amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…MARGOLIN (1942) also found that 1-rhamnose could only be utilised by Mucor ramannianus out of three Mucorales tried by him. BROCK (1951) is of the opinion that 6-carbon aldoses, glucose, mannose and galactose are much better utilised than their corresponding alcohols, sorbitol, mannitol, and dulcitol. It shows that the aldehydic or the reducing group of the sugar is necessary for their proper utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Uso tradicional o práctico: la población de la zona no reporta su uso. Sin embargo, los hongos del género Morchella tienen gran importancia económica y son objeto de comercialización por sus cualidades nutricionales (Brock 1951, Robbins & Hervey 1959, Robbins & Hervey 1965, Volk & Leonard 1989, Montoya et al 2003, Montoya et al 2004, Masaphy et al 2009, Hernández-Salmerón et al 2013. Se ha informado su consumo en 28 países de diferentes zonas del mundo (Boa 2004), por lo que no se descarta que en el futuro, este grupo sea utilizado en Colombia en el ámbito gastronómico y agroproductivo.…”
Section: Figuraunclassified